A Numerical Study of the Screening Effectiveness of Open Trenches for High-Speed Train-Induced Vibration - Chih-hung Chiang; Pei-hsun Tsai (Shock and Vibration)
This study used the 2D boundary element method in time domain to examine the screening effectiveness of open trenches on reducing vibration generated by a high-speed train. The parameters included configurations of the trench, train speed, the distance between the source and the trench, and the Poisson’s ratio of the soil. A reducing displacement level (in dB scale) was defined and used to evaluate the screening effectiveness of a wave barrier. The maximal reducing displacement level reached 25 dB when an open trench was used as a wave barrier. The depth of an open trench is a main influential parameter of screening effectiveness. The cutoff frequency of the displacement spectrum increases with decreasing trench depth. The maximal screening effectiveness occurs when the depth is 0.3-0.4 Rayleigh wavelength. Using an open trench as a wave barrier can reduce 10–25 dB of vibration amplitude at frequencies between 30 and 70 Hz. A considerable increase in screening effectiveness of the open trench was observed from 30 to 70 Hz, which matches the main frequencies of vibration induced by Taiwan High Speed Rail. The influence of trench width on screening effectiveness is nonsignificant except for frequencies from 30 to 40 Hz. Poisson’s ratio has various effects on the reduction of vibration at frequencies higher than 30 Hz.